Emotion Research in Economics - Klaus Wälde (Center for Economic Studies and ifo Institute (CESifo), 2016)
Emotions were central to the development of economics, especially in utility theory in classical economics. While neoclassical utility theory basically abolished emotions, behavioural economics more recently reintroduced emotions in utility theory. Beyond utility theory, economic theorists use emotions to explain behaviour which otherwise could not be understood or they study emotions out of interest for the emotion itself. While some analyses display a strong overlap between psychological thinking and economic modelling, in most cases there is still a large gap between economic and psychological approaches to emotion research. Ways how to reduce this gap are discussed.
Keywords: A12; B00; D03; 330; utility theory; ex-ante emotions; immediate emotions; ex-post emotions; belief-based emotions; regret; desire; stress; anxiety; guilt